Reducing the Toxicity of Radiotherapy for Pancreatic Cancer With Magnetic Resonance-guided Radiotherapy. (13th February 2020) - Tchelebi, Leila T; Zaorsky, Nicholas G; Rosenberg, Jennifer C; Sharma, Navesh K; Tuanquin, Leonard C; Mackley, Heath B; Ellis, Rodney J
Abstract: Pancreatic cancer is a highly fatal malignancy for which surgery is currently considered to be the only curative treatment. However, less than a quarter of patients have disease amenable to definitive surgical resection. Local treatment with radiation therapy is a promising alternative to surgery for those patients with unresectable disease. However, conventional radiation techniques with computed tomography (CT)-guided therapy have yielded disappointing results due to the inability to deliver ablative doses of ionizing radiation, while sparing the radiosensitive adjacent organs at risk. Magnetic resonance-guided radiotherapy (MRgRT) has emerged as an alternative to CT-guided radiation treatment which allows for the delivery of higher doses of radiation with low toxicity to surrounding structures. Further study into the use of MRgRT and dose escalation for locally advanced unresectable pancreatic cancer is needed.